Investigating the thermodynamic causes behind the anomalously large shifts in pKa values of benzoic acid-modified graphite and glassy carbon surfaces - Abiman, P.; Crossley, A.; Wildgoose, G.G.; Jones, J.H.; Compton, R.G. (American Chemical Society, 2007)
The difference between the values of 4-carboxyphenyl groups, covalently attached to either graphite (BAcarbon) or glassy carbon (BA-GC) surfaces, and benzoic acid in solution is explored using Potentiometrie titration and cyclic voltammetry. In solution, benzoic acid has a pKa of 4.20 at 25°C. However, the observed pKã value on the graphitic surfaces shows significant deviations, with BAcarbon exhibiting a large shift to higher pK a values (pKa = 6.45) in contrast to BA-GC, which is shifted to lower pKa values (pKa = 3.25). Potentiometrie titrations at temperatures between 25 and 50°C allowed us to determine the surface pKa of these materials at each temperature studied and hence to determine the enthalpy, entropy, and Gibbs' energy changes associated with the ionization of the carboxylic acid groups. It was found that the endialpic contribution is negligible and that the changes in surface pKa values are entropically controlled. This suggests that solvent ordering/disordering around the interface strongly influences the observed pKa value, which then reflects the relative hydrophobicity/hydrophilicity of the different graphitic surfaces.